Understanding Sowan as a New Paternalistic Bureaucracy Pattern of Local Officials in Indonesia - Indiahono, Dwiyanto; Satyawan, Darmanto Sahat; Yamin, Muhammad (Jurnal Bina Praja, 2022)
This study aimed to examine the visit of bureaucratic officials to local head candidates who have been confirmed to win local elections, commonly known as sowan. The officials ignore the neutrality aspect of bureaucracy that should be strictly upheld. This phenomenon is explained by the concept of a new paternalistic bureaucracy. This study used a qualitative research method with a phenomenological approach. In-depth interviews, focus group discussions (FGD), and documentation was utilized as data collection methods for this study. This study's interview and FGD participants include local officials with knowledge of the sowan phenomenon and general civil servants in Banyumas, Purbalingga, Banjarnegara, Cilacap, and Kebumen. This study discovered that sowan in the perspective of bureaucracy signifies friendship, loyalty, approach, and negotiation. This research highlights the strength of paternalistic bureaucracy, which generally begins in the final phase of the democratic process of local elections. Conceptually, this study is useful to explain the sowan phenomenon concerning bureaucratic neutrality and democracy and provide practical insights on the importance of law enforcement to violators of bureaucratic neutrality. This study explains the new paternalistic bureaucracy in the era of democracy in local governments in Indonesia. This study recommends the importance of law enforcement for violators of bureaucratic neutrality without discrimination, the improvement of the relationship between political and bureaucratic officials that reflect better partnerships in the recruitment of career officials, and the importance of bureaucrats who are committed to maintaining the principle of merit in the selection of local officials.